A randomized placebo controlled trial of the effect of preoperative statin use on matrix metalloproteinases and tissue inhibitors of matrix metalloproteinases in areas of low and peak wall stress in patients undergoing elective open repair of abdominal aortic aneurysm - Abdul Rahman, Mohd Norhisham Azmi; Khan, Junaidalam; Mazari, Fayyaz Ali Khan; Mockford, Katherine; McCollum, Peter Thomas; Chetter, Ian Clifford (Elsevier, 2011)
BACKGROUND: A double-blind, randomized controlled trial was carried out to study the effects of statins on matrix metalloproteinases (MMPs) and tissue inhibitors of matrix metalloproteinases (TIMPs) in areas of peak and low abdominal aortic aneurysm (AAA) wall stress. METHODS: A total of 40 patients undergoing elective open AAA repair were randomized to receive either atorvastatin 80 mg (n = 20) or placebo (n = 20) for 4 weeks preoperatively. Finite element analysis was used to determine AAA wall stress distribution. Full thickness aortic samples were obtained at surgery from areas of low and peak wall stress, snap-frozen, and stored at -80°C for subsequent MMP-2, -8, and -9 and TIMP-1 and -2 analyses. Statistical analysis was performed using SPSS 16.0 (SPSS Inc, Chicago, IL). RESULTS: Both groups were well matched (p > 0.05) regarding age, gender, comorbidities, and duration of hospital stay. There were no statistically significant differences in levels of MMPs and TIMPs between the statin and placebo group and between areas of low and peak AAA wall stress. CONCLUSION: The short-term use of statins is not associated in reducing levels of MMP 2, 8, and 9 and TIMP-1 and -2 in areas of low and peak wall stress in patients with AAA.